2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.27147
|View full text |Cite
|
Sign up to set email alerts
|

Using Focus Groups to Understand Military Veteran Students’ Pathways in Engineering Education

Abstract: This study examines the experiences of military veterans pursuing bachelor's degrees in engineering. Given the diverse backgrounds of veterans, their increasing numbers, and the growing national demand for engineering professionals, the timing is ideal to study the conditions under which student veterans pursue engineering education and the factors that offer them the greatest support for success. Using a comparative case study approach across three institutions,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…6,13 Our prior work found that pursuing engineering studies makes sense for military veterans who have had significant technical responsibilities as part of their service; this training provided the veterans with a practical understanding of some aspects of undergraduate engineering classwork, potentially giving them an advantage over their non-veteran peers. 5 The current study reinforces these themes and introduces new factors for consideration. The results support Zoli et al's finding that military experiences contribute to success in higher education.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…6,13 Our prior work found that pursuing engineering studies makes sense for military veterans who have had significant technical responsibilities as part of their service; this training provided the veterans with a practical understanding of some aspects of undergraduate engineering classwork, potentially giving them an advantage over their non-veteran peers. 5 The current study reinforces these themes and introduces new factors for consideration. The results support Zoli et al's finding that military experiences contribute to success in higher education.…”
Section: Discussionsupporting
confidence: 67%
“…For example, there is now a separate session specifically designed to provide information about higher education opportunities. As reported here and in a previous study, 5 given the link between a desire for financial security and choosing the engineering pathway, perhaps this session could include explicit information about salary and long-term career opportunities in engineering fields, among others.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Neal's comment that was supported by the other male veterans suggests that while providing a space for venting frustrations may certainly be helpful, social intervention programs involving the broader faculty and student populations may be needed to help ameliorate biased attitudes towards veteran students. This sentiment is moderately supported by a recent study by Main et al (2016) who mentioned anecdotally from their interviews of 21 veterans that some respondents (the number was not reported) chose to not disclose their status as a veteran, preferring "to 'hide' their veteran status, or at least relegate it to secondary status, as compared to their other statuses (e.g., parent, engineering major, etc.)" (p.8).…”
Section: Discussionmentioning
confidence: 94%
“…We are disseminating our work at the ASEE Annual Conference in the new Military and Veterans (MV) Division which will have papers presented for the first time in 2016. 4 We are also presenting our work in a session at the NASPA Veterans conference in February 2016 5 and at the Southern Sociological Society meeting in April 2016.…”
Section: Future Workmentioning
confidence: 99%